Improving the security and privacy in Malaysia academic digital libraries - Zainol, Zairul Nizam; Mat Yatin, Saiful Farik; Abdullah Sani, Mad Khir Johari (Faculty of Information Management, 2025)
Digital libraries have become an important and valuable platform because they provide easy access to various information and resources that users need. However, as the digital world continues to develop and the technological revolution and so-called technology disruption, becomes increasingly complex, concerns have emerged about the risk of cyber threats and their impact on user privacy and security when accessing digital libraries. Therefore, the objectives of this study focus on present key issues facing digital libraries in relation to privacy and security, evaluating the capacity of digital libraries to respond to emerging threats by studying their preparedness, and seeing if there are current policies or guidelines used by digital libraries in combating the cyber threats. The study outcome suggests developing a strategy for enhancement by looking at three areas, improving the current framework, producing new guidelines or policy suits for digital libraries, and developing a prototype based on AI technology to mitigate the cyber threats.